Emergency sandwich patch repair via right ventricular incision for postinfarction ventricular septal defects: a case series. Issue 5 (17th May 2021) - Shimahara, Yusuke; Fukushima, Satsuki; Yajima, Shin; Tadokoro, Naoki; Kakuta, Takashi; Asaumi, Yasuhide; Kobayashi, Junjiro; Fujita, Tomoyuki
Abstract: Background: The surgical treatment for postinfarction ventricular septal defect (VSD) remains challenging, especially in emergency cases. Several authors have reported the efficacy of a sandwich patch VSD repair via a right ventricular (RV) incision. However, this procedure remains uncommon, and its efficacy is still unknown, especially when performed under an emergency. Case summary: We were able to perform sandwich patch VSD repair via an RV incision on seven consecutive patients with VSD following an ST-segment elevation myocardial infarction (STEMI) from March 2017 to December 2019. Bovine pericardial patches were used for sandwich patches. Two patients developed inferior STEMI, and the other patients developed anterior STEMI. Six patients received intra-aortic balloon pump prior to surgery, and the other received extracorporeal membrane oxygenation with Impella. The interval between the diagnosis of VSD and surgery was within 1 day in all patients except one (5 days). All seven patients underwent VSD repair in the emergency status. Four patients underwent concomitant coronary artery bypass grafting. The hospital mortality rate was 14.3% (1/7). Early postoperative transthoracic echocardiography revealed that only one patient developed more than trace residual shunt. The postoperative right atrial pressure was not significantly elevated at ≤12 mmHg in all patients. No patient developed early postoperative prolonged low cardiac output syndrome. Discussion: In patients with postinfarction VSD, a sandwich patch VSD repair via an RV incision is a promising procedure with a low incidence of residual shunt development and hospital mortality, even in emergency cases.